2014
DOI: 10.4018/ijoci.2014040104
|View full text |Cite
|
Sign up to set email alerts
|

Towards Trust and Trust Building in a Selected Cloud Gaming Virtual Community

Abstract: Trust is an increasingly important factor in the virtual communities (VCs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The purpose of this paper is to further extend our previous study (Yao and Chang, 2014), whereby a Chinese game was identified and illustrated as a case study for our investigation. Four major hypotheses based on the literature review were set up with its respective questionanaires presented.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The purpose of this paper is to further extend our previous study (Yao and Chang, 2014), whereby a Chinese game was identified and illustrated as a case study for our investigation. Four major hypotheses based on the literature review were set up with its respective questionanaires presented.…”
Section: Introductionmentioning
confidence: 94%
“…We elaborate that under each category of trust, there are related literature with explanations about how they are developed into each hypotheses. In summary of our previous work (Yao and Chang, 2014), the hypotheses are presented as follows.…”
Section: The Hypotheses Of Trusts and The Extension From Our Previousmentioning
confidence: 99%
See 1 more Smart Citation
“…Yao and Chang [19] collected 100 valid samples to analyze trust between different members in virtual communities. They found that the trust and friendship they have developed can be essential for community building and business opportunities.…”
Section: Research Meansmentioning
confidence: 99%
“…With the rise of Cloud Computing, gaming can be provided as a 24/7 service for anyone to take part at any time provided with fast optic fibre network and excellent computing resources. Cloud gaming offers businesses with these three models: subscription; pay-as-you-go and products only (Yao and Chang, 2014). A subscription model is a model to pay monthly to ensure players can access games.…”
Section: Cloud Gamingmentioning
confidence: 99%